Protocol for a global menopause priority setting partnership - Jane Daniels; Gita Mishra; Sharon Dixon; Martha Hickey; Zachary Nash; Michelle Peate; Claire Hardy; Shibani Nicum; Sarah Hillman; Andrew Fisher; Toto Gronlund; Hadine Joffe; et al. (BMJ Open)
Introduction All those born with functioning ovaries will eventually experience menopause, and many will be symptomatic. However, significant gaps in the evidence base for menopause care remain. This National Institute for Health and Care Research James Lind Alliance Menopause Priority Setting Partnership (MAPS) will engage with clinicians and those with lived experience globally to determine the leading priorities for future menopause research.Methods and analysis MAPS will follow the established James Lind Alliance methodology which has already resulted in over 100 ‘top 10’ research priorities across health domains. It will be led by a steering group comprised of clinicians and lived experience members. Leveraging the networks of steering group members and partner organisations, the priority setting partnership will identify evidence uncertainties using an online survey. Evidence checking will be undertaken to determine which questions have already been answered. Prioritisation will be done in two stages, initially by online survey and then at a face-to-face workshop.Ethics and dissemination Ethical approval was not required. The final top 10 priorities for menopause, as ranked by stakeholders at the final consensus workshop, will be disseminated in the relevant peer-reviewed journals. A final report will be available on the MAPS and James Lind Alliance websites. The leading priorities will inform the future global research agenda for menopause.